IMPLEMENTASI MODEL PEMBELAJARAN SEJARAH THINK PAIR SHARE PADA PESERTA DIDIK KELAS XI IPA 2 MAN 1 BANJARMASIN - Nazarwaty Nazarwaty (Universitas Lambung Mangkurat, 2017)
This study aimed to describe the implementation model of teaching history of type Think Pair Share (TPS). Activities learners about analyzing the change of government of guided democracy until the birth of the New Order in class XI IPA 2 MAN 1 Banjarmasin with application-type learning model Think Pair Share (TPS). The study of students about analyzing the change of government of guided democracy until the birth of the New Order in class XI IPA 2 MAN 1 Banjarmasin. Teachers should implement a variety of active learning in the classroom that will further improve the activity and motivation of learners in the teaching of history. It is expected that the history teacher to make cooperative learning model Think Pair Share as an alternative in implementing the learning, particularly in the matter of democracy terpimin until the birth order Barudan other material that can be applied to this model, so as to improve the learning outcomes of students. Teachers should be able to provide guidance, oversight and guidance to students so that maximum activeness and creativity of learners in learning optimal. Learners should increase activity and learning outcomes, especially in the teaching of history.Keywords: learning model type of think pair share, guided democracy, the new orderPenelitian ini bertujuan untuk mendeskripsikan implementasi model pembelajaran sejarah tipe Think Pair Share (TPS). Aktivitas peserta didik tentang menganalisis pergantian pemerintahan dari demokrasi terpimpin sampai lahirnya Orde Baru di kelas XI IPA 2 MAN 1 Banjarmasin dengan penerapan model pembelajaran tipe Think Pair Share (TPS). Hasil belajar peserta didik tentang menganalisis pergantian pemerintahan dari demokrasi terpimpin sampai lahirnya Orde Baru di kelas XI IPA 2 MAN 1 Banjarmasin. Guru sebaiknya menerapkan berbagai pembelajaran aktif di dalam kelas sehingga akan lebih meningkatkan keaktifan dan motivasi peserta didik dalam pembelajaran sejarah. Diharapkan kepada guru sejarah untuk menjadikan model pembelajaran kooperatif tipe Think Pair Share sebagai alternatif dalam melaksanakan pembelajaran, khususnya pada materi demokrasi terpimin sampai lahirnya orde barudan materi lainnya yang dapat diterapkan dengan model pembelajaran ini, sehingga dapat meningkatkan hasil belajar peserta didik. Guru hendaknya dapat memberikan bimbingan, pengawasan dan pengarahan yang maksimal kepada peserta didik agar keaktifan dan kreativitas peserta didik dalam pembelajaran berjalan optimal. Peserta didik sebaiknya meningkatkan aktivitas dan hasil belajar terutama pada pembelajaran sejarah.Kata Kunci: model pembelajaran tipe think pair share, demokrasi terpimpin, orde baru